Techniques for electronic resource management : TERMS and the transition to open - Emery, Jill (ALA Editions, 2020)
"Growing open access options, big-deal price pressure, fluid ebook purchasing models. You need a framework for managing the many details of your online material. TERMS - Techniques for Electronic Resource Management Systems-gave you one. Now its creators, mining 5 years of notes and with input from many voices in the field, have updated their influential life cycle model. In six sections you will circle through selection, procurement and licensing, implementation, troubleshooting, evaluation, and preservation and sustainability. The book's structure supports easy reference whether a single team manages electronic resources or if responsibility is spread across the library organization. Each section breaks into six categories which in turn give guidance in three areas: Basic (80 percent of issues with electronic resources), Complex, and the growing universe of Open Access resources"--